Strategies for Improvement of Government Budget Absorption of Bogor City - Gustawan Rachman; Ma mun Sarma; Dwi Rachmina (Journal of Social Science, 2020)
This study aims to analyze for factors that cause delays in the absorption of the Bogor City Government's expenditure budget so that a strategy can be formulated to improve the performance of this budget absorption. Searching for variables forming the causal factors is done by using primary data sourced from Dinas Kesehatan and Sekretariat Daerah, based on the researcher's work experience when assigned to the Finance Section and the Planning and Reporting Division of Dinas Kesehatan and Bagian Pengadaan Barang dan Jasa Sekretariat Daerah Kota Bogor for approximately 10 years of the assignment period and library data search. Exploratory Factor Analysis (EFA) is used to look for underlying factors extracted from the factors forming variables. The search foralternative strategies to improve performance of budget absorption was carried out using the Analytic Hierarchy Process (AHP). The EFA analysis found five main factors causing delays in the absorption of budget expenditure, namely factor in budget planning activities, factor in government regulation and bureaucracy, factor of work conditions, factor influencing financial activities and disbursement of the Government budget, and human resources of the state civil apparatus (ASN). AHP analysis shows that of the five leading sectors of the Regional Apparatus that play a role as key leaders in improving the performance of budget absorption is Sekretariat Daerah. The main obstacle in improving budget absorption is internal and external intervention. The main strategy to correct delays inspending is to improve quality of budget planning and procurement of service goods.